-3(2y+3)=-10(y+3)

Simple and best practice solution for -3(2y+3)=-10(y+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(2y+3)=-10(y+3) equation:



-3(2y+3)=-10(y+3)
We move all terms to the left:
-3(2y+3)-(-10(y+3))=0
We multiply parentheses
-6y-(-10(y+3))-9=0
We calculate terms in parentheses: -(-10(y+3)), so:
-10(y+3)
We multiply parentheses
-10y-30
Back to the equation:
-(-10y-30)
We get rid of parentheses
-6y+10y+30-9=0
We add all the numbers together, and all the variables
4y+21=0
We move all terms containing y to the left, all other terms to the right
4y=-21
y=-21/4
y=-5+1/4

See similar equations:

| x²-4x-88=0 | | -(x+2)=4(x+1) | | 9/p-10=2/4+p | | 28=x+164 | | -6(1+v)=2(1+-3v)+-8 | | G(0)=x*2+3 | | 3n+20=4n-7 | | b-6/3=1 | | 6=-5(c+4)=10 | | –8=u−42/–7 | | d+1/2=-2 | | 6p+10=-56 | | 62=12x+10 | | G(-2)=x*2+3 | | −8.5x+0.22=−3.18 | | 3(x-6)-8x=-2+5(2+5(2x1) | | 56=12x+10 | | -39+3a=(2a-8) | | y+6/3=-4 | | 51=3(t-56) | | 8^x/5=23 | | 3x/7-x/5=2/35 | | 3n+2n-1=2 | | |-8x+20|=|2x+40| | | 12x-5-3x=+35 | | G(3)=x*2+3 | | 7x²+3x-10=0 | | 36=t/8+33 | | 24=n/2+20 | | 18=3(p-10) | | 59=12x+10 | | 4r^2-8r=-12 |

Equations solver categories